Internalisasi Nilai Kemandirian Pada Anak Anak Komunitas Tanoker di Jember (The Internalization of Independence Value toward Children of Tanoker Community in Jember) - Mu’allifin, Isnatul; Hidayat, Nurul (Laboratorium Sosiologi FISIP Universitas Jember, 2020)
This paper focuses on analyzing the internalization process in building independence character among children of the Tanoker Community. The way to support the internalization process includes respecting children's initiatives, respecting children in determining interests, training children's courage to act, maximizing children's abilities, and building closeness with children. These values ​​are studied using the social construction theory of Peter L. Berger. This theory is relevant to the issues discussed because internalization in a person occurs through interactions with other people. The internalization occurs through an externalization and objectification process. By using qualitative research approaches, constructivist paradigms, data in this study are descriptive or narrative. The technique of determining informants in this study uses purposive sampling until 15 key informants, and 20 supporting informants are found. Data collection was carried out through participatory observation, in-depth interviews, documentation, and literature studies. Data analysis was performed using the Miles and Huberman analysis method, which is through the stages beginning with data reduction, data display, conclusion drawing / verification. The results of the practices carried out by Tanoker in supporting the process of internalizing the value of independence in children bring children in a level of being more courageous, confident, active, dare to make choices, and dare to express themselves. When they are independent or sovereign in thinking and acting, they have become independent by trusting and relying on their abilities. Keywords: Children, Tanoker Community, Internalization Process, Independence Tulisan ini berfokus pada internalisasi nilai-nilai kemandirian pada anak yang ada di Komunitas Tanoker. Cara-cara yang dilakukan untuk mendukung proses internalisasi diantaranya dengan menghargai inisiatif anak, menghargai anak dalam menentukan minat, melatih keberanian anak untuk bertindak, memaksimalkan kemampuan anak, serta membangun kedekatan dengan anak. Tujuan dari adanya internalisasi nilai kemandirian dalam diri anak adalah membentuk pribadi mandiri dalam diri anak-anak. Nilai nilai ini dikaji menggunakan teori konstruksi sosial dari Peter L Berger. Metodologi penelitian yang digunakan adalah fenomenologi dan data dalam penelitian ini bersifat deskriptif. Teknik penentuan informan dalam penelitian ini menggunakan purposive sampling hingga ditemukan informan utama 15 orang dan 20 informan pendukung. Pengumpulan data dilakukan melalui observasi partisipatoris, in dept interview, dokumentasi, dan studi literatur. Pengujian keabsahan data dilakukan dengan metode triangulasi. Hasil dari cara-cara yang dilakukan komunitas tanoker dalam mendukung proses internalisasi nilai kemandirian pada anak membawa anak-anak dalam taraf menjadi pribadi yang lebih berani, percaya diri, aktif, mandiri dalam membuat pilihan, serta berani mengekspresikan diri. Semua itu yang pada akhirnya membawa anak-anak pada kedaulatan berfikir dan bertindak. Ketika mereka telah merdeka atau berdaulat dalam berfikir dan bertindak berarti mereka telah mandiri dengan mempercayai dan bergantung kepada kemampuan diri mereka sendiri. Kata Kunci: Anak-anak, Komunitas Tanoker, Internalisasi Nilai, Kemandirian